Substantially elevating the levels of αB‐crystallin in spinal motor neurons of mutant SOD1 mice does not significantly delay paralysis or attenuate mutant protein aggregation. (26th January 2015) - Xu, Guilian; Fromholt, Susan; Ayers, Jacob I.; Brown, Hilda; Siemienski, Zoe; Crosby, Keith W.; Mayer, Christopher A.; Janus, Christopher; Borchelt, David R.
Abstract There has been great interest in enhancing endogenous protein maintenance pathways such as the heat‐shock chaperone response, as it is postulated that enhancing clearance of misfolded proteins could have beneficial disease modifying effects in amyotrophic lateral sclerosis and other neurodegenerative disorders. In cultured cell models of mutant SOD1 aggregation, co‐expression of αB‐crystallin (αB‐crys) has been shown to inhibit the formation of detergent‐insoluble forms of mutant protein. Here, we describe the generation of a new line of transgenic mice that express αB‐crys at > 6‐fold the normal level in spinal cord, with robust increases in immunoreactivity throughout the spinal cord grey matter and, specifically, in spinal motor neurons. Surprisingly, spinal cords of mice expressing αB‐crys alone contained 20% more motor neurons per section than littermate controls. Raising αB‐crys by these levels in mice transgenic for either G93A or L126Z mutant SOD1 had no effect on the age at which paralysis developed. In the G93A mice, which showed the most robust degree of motor neuron loss, the number of these cells declined by the same proportion as in mice expressing the mutant SOD1 alone. In paralyzed bigenic mice, the levels of detergent‐insoluble, misfolded, mutant SOD1 were similar to those of mice expressing mutant SOD1 alone. These findings indicate that raising the levels of αB‐crys in spinal motor neurons by 6‐fold does not produce the therapeutic effects predicted by cell culture models of mutant SOD1 aggregation. <boxed-text content-type="graphic" id="jnc13022-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Enhancing the protein chaperone function may present a therapeutic approach to amyotrophic lateral sclerosis caused by mutations in SOD1, and other neurodegenerative disorders characterized by cytosolic protein aggregation. Previous studies in cell models suggested that the chaperone known as αB‐crystallin (αB‐crys) can prevent mutant SOD1 aggregation. We report that transgenic expression of αB‐crys at > 6‐fold the normal level in spinal cords of mice expressing mutant SOD1 produces no therapeutic benefit.